Analisis Budaya Keselamatan Pasien pada Berbagai Tenaga Kesehatan di RSUD dr. Soediran Mangun Sumarso Kabupaten Wonogiri - Dwi Suranto; Chriswardani Suryawati; Yuliani Setyaningsih (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2020)
Patient safety incidents at a hospital still occur at almost 92.1% near-miss events, 4.3% harmful incidents, 2.4% no-harm incidents and 1.2% unintended events. At the General District Hospital of dr. Soediran Mangun Sumarso, the hospital manager has not understood the function of reporting system so that there is no follow up. Even, blaming culture still happens, and not all health workers care about incident reporting. Establishing a patient safety culture is the first step to implement a patient safety program. This study was intended to analyze a patient safety culture among health workers.This study was conducted at the General District Hospital of dr. Soediran Mangun Sumarso which is a type-B hospital. This study was analytic with a cross-sectional design. It involved 228 health workers as respondents, used Kruskal Wallis for the analysis and adopted instruments from the Hospital Survey on Patient Safety Culture (HSOPSC). The findings explained that communication openness dimension is in the middle category. Teamwork in the units is good, and the overall perception is moderate. Staffing is moderate, so id non-punitive response. The reporting frequency is moderate with 43.8% respondents who said not reporting any incidents for the past 12 months. The organizational learning is good, and the staff expectation is moderate. The level of patient safety is good, and the feedback is moderate. Transfer and transition are good. The p-values for staff expectation, organizational learning, unit tea work, openness, and feedback are 0.001, 0.017, 0.004, 0.000, and 0.039 respectively. Whereas the non-punitive response has a p-value of 0.001, staffing has a p-value of 0.005, and management support results in a p-value of 0.001. Teamwork among units has a p-value of 0.001 and transfer and transition performs p-value of 0.004.There are some differences among health workers in terms of communication openness with a p-value of 0.000.